The invisible blackness of Harryette Mullen's poetry: writing, miscegenation and what remais to be seen - Amorim, Lauro Maia [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This essay addresses the poetics of Harryette Mullen, an awarded African-American female poet whose work questions the boundaries that shape the expectations for accessible intelligibility in African-American literature. Mullen’s poems skirt the edges of intelligibility by going beyond the expectations for a visible/intelligible form of language that would embrace the experience of blackness. I argue that writing in Mullen’s poetry works as process of miscegenation by playing on the illegibility of blackness, beyond a visible line of distinction between what is or should be considered part of blackness itself, which engages new forms of reflection on poetry as a politically meaningful tool for rethinking the role of the black (female) poet within the black diaspora.

Este ensaio aborda a poética de Harryette Mullen, poetisa afro-americana cuja obra questiona os limites que moldam as expectativas pela inteligibilidade acessível na literatura afro-americana. Os poemas de Mullen exploram as bordas da inteligibilidade, avançando para além das expectativas por uma forma visível/inteligível de linguagem que abarcaria a experiência da negritude. Argumenta-se que a escrita na poesia de Mullen funciona como um processo de miscigenação ao jogar com a ilegibilidade da negritude, para além de uma linha visível de distinção entre o que é ou que deveria ser considerado como parte apropriada da negritude, o que possibilita novas formas de reflexão sobre a poesia como um instrumento politicamente significativo para se repensar o papel da poetisa e do poeta negros no espaço da diáspora negra.
A negritude invisível da poesia de Harryette Mullen: escrita, miscigenação e o que resta ser visto
Keywords: Harryette Mullen; Poesia; Escrita; Miscigenação; (In)visibilidade; Harryette Mullen; Poetry. Writing; Miscegenation; (In)visibility